Computational Study of Fe(II) Complex Compound Structure Prediction with Thiocyanate (SCN-) and Pyridin (C5H5N) Ligands Using the RHF (Restricted Hartree Fock) - Vivi Semari Malau; Asep Wahyu Nugraha (Universitas Negeri Medan, 2025)
The formation of Fe(II) complex compounds with thiocyanate (SCN-) as well as pyridin (C5H5N) forms a tetrapyridinditiocyanateobesi(II) complex compound, [Fe(SCN)2(py)4]. The comparison of these complex compounds is still engineering, so the researchers examined the comparison of the structure of stable complex compounds on Fe(II) with thiocyanate and pyridin ligands, by continuing previous research using computational chemistry. Complex compounds that are more stable and the most suitable molecular formula based on computational calculations using RHF hybrid functions and 6- 31G basis sets, geometry optimization of molecules from NWChem version 6.6 and Jmol software version 14.28.29. The energy of the computational calculation using RHF/6-31G for the structure Fe(SCN)2(C₅H₅N)4: -1524.86976182444 KJ/mol; Fe(SCN)3(C₅H₅N)3 structure: -1557.98302881166 KJ/mol; and Fe(SCN)4(C₅H₅N)2 structure: -2083.53616162888 KJ/mol. The change in formation energy indicates that the structure of Fe(SCN)4(C₅H₅N)2 is the most stable. The most suitable molecular formula for the Fe(II) complex compound is [Fe(SCN)4(C₅H₅N)2].